The effects of culture conditions on the glycosylation of secreted human placental alkaline phosphatase produced in Chinese hamster ovary cells - Jong Hyun Nam; Fuming Zhang; Myriam Ermonval; Robert J. Linhardt; Susan T. Sharfstein (2008)
The effects of different culture conditions, suspension and microcarrier culture and temperature reduction on the structures of N-linked glycans attached to secreted human placental alkaline phosphatase (SEAP) were investigated for CHO cells grown in a controlled bioreactor. Both mass spectrometry and anion-exchange chromatography were used to probe the N-linked glycan structures and distribution. Complex-type glycans were the dominant structures with small amounts of high mannose glycans observed in suspension and reduced temperature cultures. Biantennary glycans were the most common structures detected by mass spectrometry, but triantennary and tetraantennary forms were also detected. The amount of sialic acid present was relatively low, approximately 0.4 mol sialic acid/mol SEAP for suspension cultures. Microcarrier cultures exhibited a decrease in productivity compared with suspension culture due to a decrease in both maximum viable cell density (15-20%) and specific productivity (30-50%). In contrast, a biphasic suspension culture in which the temperature was reduced at the beginning of the stationary phase from 37 to 33 degrees C, showed a 7% increase in maximum viable cell density, a 62% increase in integrated viable cell density, and a 133% increase in specific productivity, leading to greater than threefold increase in total productivity. Both microcarrier and reduced temperature cultures showed increased sialylation and decreased fucosylation when compared to suspension culture. Our results highlight the importance of glycoform analysis after process modification as even subtle changes (e.g., changing from one microcarrier to another) may affect glycan distributions.